Inovasi Produk dan Layanan Halal sebagai Strategi Menangani Isu Keberlanjutan dan Perubahan Iklim Global - Dinda Novaberliana Putri; Hendri Hermawan Adinugraha (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the strategic role of halal product and service innovation in addressing sustainability and global climate change issues. Using a literature review approach, the article synthesizes academic sources and industry reports to evaluate the halal industry's contribution to sustainable development agendas. The findings reveal that halal innovation has expanded across sectors such as food, cosmetics, pharmaceuticals, tourism, logistics, and Islamic finance, supported by technologies like blockchain and green finance. These innovations enhance transparency, efficiency, and global competitiveness. Despite challenges faced by halal MSMEs, including limited access to technology and certification regulations, the integration of circular economy principles and the Halal Value Chain offers inclusive and adaptive growth opportunities. The study concludes that synergy between halal innovation and the Sustainable Development Goals (SDGs), particularly SDG 12 and SDG 13, can strengthen a competitive and sustainable halal ecosystem. Practical recommendations are provided for business actors, regulators, and academics to foster cross-sector collaboration in building an ethical and environmentally friendly halal industry.